Development of a Roblox-Based Interactive Game for Arabic Vocabulary Learning in Islamic Senior High Schools - Siti Jubaidah; Mohamad Sarip; Siti Masyitoh; Ahmad Rasyadan Rafif; Wafa Menasri (UIN Sunan Gunung Djati Bandung, 2026)
Arabic vocabulary mastery is essential for language proficiency, yet many Islamic senior high school students still struggle with conventional memorization-based instruction. Although immersive game-based learning has gained attention, empirical studies on Roblox for Arabic vocabulary instruction remain scarce, particularly in formal Islamic senior high schools. This study aimed to develop and evaluate an interactive Roblox game as a supplementary learning medium for Arabic vocabulary instruction. A Research and Development (R&D) approach employing the Four-D model (define, design, develop, and disseminate) was adopted. The participants consisted of 21 eleventh-grade students of Islamic Senior High School As-Syafi’iyah 02, Bekasi, and two expert validators. Data were collected through observations, interviews, questionnaires, and validation sheets, and analyzed using descriptive qualitative and quantitative techniques. The needs analysis revealed a strong demand for interactive learning media, with students expressing positive attitudes toward digital game-based learning. Based on these findings, a Roblox-based game, Pocket Arabic, was developed by integrating curriculum-aligned vocabulary materials, contextual learning tasks, challenges, rewards, and immediate feedback. Expert evaluation demonstrated high feasibility, with scores of 100% for content validity and 86% for media quality. Student responses reached 66.29%, indicating generally positive acceptance despite technical limitations. These findings suggest that Roblox is a feasible supplementary medium for Arabic vocabulary learning and offers practical contributions to technology-enhanced Arabic language education in Islamic Senior High Schools.